Security and cross-border political crime: the formation of transnational security regimes in 18th and 19th century Europe = Sicherheit und grenzübergreifende politische Kriminalität: die Formierung transnationaler Sicherheitsregime in Europa im 18. und 19. Jahrhundert - Härter, Karl (2013)
"This contribution proposes to observe Foucault's concept of the security dispositive from the angle of transnational security and criminal law regimes. Since the late 18th century security and securitization became not only a prime category and field of national policies and discourses but were increasingly influenced by transnational issues and cross-border security threats (or narratives) such as international crime, transnational political violence and international conspiracies. This was accompanied by the formation of transnational security regimes, which concerned cross-border security policies, discourses and legal norms in the fields of extradition, political asylum, and police cooperation, with a variety of different actors: states, police organizations, experts, international organizations. These transnational security regimes and their respective fields were characterized by complex interdependencies and interactions as well as by legal pluralism, flexibility, fragmenta